The nucleation fraction of local volume galaxies. Issue 3 (16th August 2021) - Hoyer, Nils; Neumayer, Nadine; Georgiev, Iskren Y; Seth, Anil C; Greene, Jenny E
ABSTRACT: Nuclear star clusters (NSCs) are a common phenomenon in galaxy centres and are found in a vast majority of galaxies of intermediate stellar mass ≈ 10^9 M_ . Recent investigations suggest that they are rarely found in the least and most massive galaxies and that the nucleation fraction increases in dense environments. It is unclear whether this trend holds true for field galaxies due to the limited data currently available. Here we present our results on the nucleation fraction for 601 galaxies in the Local Volume (12 Mpc ). Covering more than eight orders of magnitude in stellar mass, this is the largest sample of galaxies analysed in a low-density environment. Within the Local Volume sample we find a strong dependence of the nucleation fraction on galaxy stellar mass, in agreement with previous work. We also find that for galaxies with M_ 10^9 M_, early-type galaxies have a higher nucleation fraction than late-types. The nucleation fraction in the Local Volume correlates independently with stellar mass, Hubble type, and local environmental density. We compare our data to those in galaxy cluster environments (Coma, Fornax, and Virgo) by compiling previous results and calculating stellar masses in a homogeneous way. We find significantly lower nucleation fractions (up to 40 per cent) in galaxies with M_ 10^9.5 M_, in agreement with previous work. Our results reinforce the connection between globular clusters and NSCs, but it remains unclear if it can explain the observed trends with Hubble type and local environment. We speculate that correlation between the nucleation fraction and cluster environment weakens for the densest clusters like Coma and Virgo.